HLA–B27 Alters the Response to Tumor Necrosis Factor α and Promotes Osteoclastogenesis in Bone Marrow Monocytes From HLA–B27–Transgenic Rats. Issue 8 (26th July 2013) - Layh‐Schmitt, Gerlinde; Yang, Eva Y.; Kwon, Grace; Colbert, Robert A.
<x xml:space="preserve">Abstract</x> Objective To determine whether HLA–B27 expression alters the response of bone marrow monocytes from HLA–B27/human β2‐microglobulin–transgenic (B27‐Tg) rats to tumor necrosis factor α (TNFα) and, if so, whether this affects the cells involved in bone homeostasis. Methods Bone marrow monocytes were treated with RANKL or with TNFα to promote osteoclast formation. Osteoclasts were quantified by counting. Gene expression was measured using quantitative polymerase chain reaction analysis, and protein was detected by enzyme‐linked immunosorbent assay, immunoblotting, or immunofluorescence. Effects of endogenously produced cytokines on osteoclast formation were determined with neutralizing antibodies. Results TNFα treatment enhanced osteoclast formation 2.5‐fold in HLA–B27–expressing cells as compared to wild‐type or to HLA–B7/human β2‐microglobulin–expressing monocytes. TNFα induced ∼4‐fold up‐regulation of HLA–B27, which was associated with the accumulation of misfolded heavy chains, binding of the endoplasmic reticulum (ER) chaperone BiP, and activation of an ER stress response, which was not seen with HLA–B7. No differences were seen with RANKL‐induced osteoclastogenesis. Enhanced interleukin‐1α (IL‐1α) production from ER‐stressed bone marrow monocytes from B27‐Tg rats was found to be necessary and sufficient for enhanced osteoclast formation. However, bone marrow monocytes from B27‐Tg rats also produced more interferon‐β (IFNβ), which attenuated the effect of IL‐1α on osteoclast formation. Conclusion HLA–B27–induced ER stress alters the response of bone marrow monocytes from B27‐Tg rats to TNFα, which is associated with enhanced production of IL‐1α and IFNβ, cytokines that exhibit opposing effects on osteoclast formation. The altered response of cells expressing HLA–B27 to proinflammatory cytokines suggests that this class I major histocompatibility complex allele may contribute to the pathogenesis of spondyloarthritis and its unique phenotype through downstream effects involving alterations in bone homeostasis.